2020
DOI: 10.1007/s11356-020-08661-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular background of cadmium tolerance in Rht dwarf wheat mutant is related to a metabolic shift from proline and polyamine to phytochelatin synthesis

Abstract: Plant height is among the most important agronomic traits influencing crop yield. Wheat lines carrying Rht genes are important in plant breeding due to their both higher yield capacity and better tolerance to certain environmental stresses. However, the effects of dwarf-inducing genes on stress acclimation mechanisms are still poorly understood. Under the present conditions, cadmium stress induced different stress responses and defence mechanisms in the wild-type and dwarf mutant, and the mutant with the Rht-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Increased proline accumulation is one of the defense mechanisms that plants have developed to counteract the harmful effects of adverse environmental condition stresses such as drought, salinity, and hypoxia [ 9 , 11 , 62 , 63 ]. Under Cd stress, however, the changes in proline concentration are often contradictory, especially in the leaves [ 33 , 34 , 35 , 36 , 37 , 64 ]. Therefore, we examined the changes over time of proline concentration in individual leaves, differing in developmental stage and age, during the first 48 h after the application of Cd ions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased proline accumulation is one of the defense mechanisms that plants have developed to counteract the harmful effects of adverse environmental condition stresses such as drought, salinity, and hypoxia [ 9 , 11 , 62 , 63 ]. Under Cd stress, however, the changes in proline concentration are often contradictory, especially in the leaves [ 33 , 34 , 35 , 36 , 37 , 64 ]. Therefore, we examined the changes over time of proline concentration in individual leaves, differing in developmental stage and age, during the first 48 h after the application of Cd ions.…”
Section: Discussionmentioning
confidence: 99%
“…Although accumulation of proline under osmotic stress is a well-known phenomenon, the results describing the changes in proline concentration due to cadmium toxicity are often contradictory, especially in the leaves. Cadmium has been found to significantly increase proline accumulation in the leaves of sunflower [ 33 ], cucumber [ 34 ], and bean seedlings [ 35 ], while reduced proline concentration was observed in the leaves of oilseed rape [ 36 ], wheat [ 37 ], and hybrid poplar [ 38 ]. The influence of cadmium on proline concentration was investigated after several days or weeks of treatment; hence, differences may have resulted from the differing roles of this multifunctional amino acid [ 11 ] at individual stages of adaptation to unfavorable conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of candidate reference genes were chosen based on existing literature that utilised them as suitable stable internal control genes for qRT-PCR analysis in different plant species [18,21,28,41]. The applicability of ADPR (Unigene cluster: Ta30797) and PGD (Unigene cluster: Ta2291) (candidate reference genes proposed by Paolacci et al [27]) were confirmed previously by our research group in wheat (Triticum aestivum L.) under different stress conditions [40,[42][43][44]. For primer design, known wheat sequences were chosen either from NCBI Gene Bank or in the case of ADPR and PGD the corresponding sequences were obtained from NCBI-Unigene database.…”
Section: Reference Gene Selection and Pcr Primer Designmentioning
confidence: 92%
“…The majority of candidate reference genes were chosen based on their description being stable internal control genes for qRT-PCR analysis in different plant species ( [10,13,19,34]. The applicability of ADPR (Unigene cluster: Ta30797) and PGD (Unigene cluster: Ta2291) (candidate reference genes proposed by [20]) were con rmed previously by our research group in wheat (Triticum aestivum L.) under different stress conditions [33,[35][36][37]. For primer design, known wheat sequences were chosen either from NCBI Gene Bank or in the case of ADPR and PGD the corresponding sequences were obtained from NCBI-Unigene database.…”
Section: Reference Gene Selection and Pcr Primer Designmentioning
confidence: 99%